Hubungan Tingkat Pengetahuan Perawat Tentang Keselamatan Pasien Dengan Kepatuhan Terhadap Prinsip 7 Benar Dalam Pemberian Obat di Ruang Rawat Inap RS Khusus Bedah Columbia Asia Semarang - Kusriyati Kusriyati; Rahayu Winarti (Journal of Health, Medical, and Psychological Studies, 2026)
This study examines the relationship between nurses’ knowledge of patient safety and their compliance with the seven rights principle of medication administration in an inpatient setting at a specialized surgical hospital in Semarang. A quantitative empirical approach with a cross-sectional correlational design was employed, involving 54 nurses selected through total sampling. Data were collected using structured questionnaires and observational checklists, and analyzed using Spearman rank correlation. The findings indicate a statistically significant positive correlation with moderate strength, suggesting that higher levels of knowledge are associated with better compliance in medication practices. The results highlight that knowledge functions as a critical cognitive foundation influencing clinical behavior and adherence to safety protocols. However, variations in compliance suggest the involvement of additional factors such as workload, organizational support, and patient safety culture. These findings emphasize the need for integrated strategies combining continuous education, clinical supervision, and system-level interventions to enhance patient safety outcomes. Strengthening institutional policies and fostering a safety-oriented environment are essential to reduce medication errors and improve healthcare quality.